2018
DOI: 10.4149/bll_2017_119
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of thymoquinone over olanzapine-induced side effects in liver, and metabolic side effects

Abstract: OBJECTIVES: The aim of the study was to investigate the possible protective qualities of thymoquinone (TQ) against the side-effects of olanzapine (OLZ) in an experimental model in rat liver with histologic and biochemical assessments. METHODS: Experimental procedures were performed on 35 female Sprague Dawley rats. Rats were randomly divided into fi ve groups as: group 1: control; group 2: OLZ; group 3: OLZ+TQ-1; group 4: OLZ+TQ-2; and group 5: OLZ+TQ-3. RESULTS: The results showed that a 2-week administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The results of our study displayed that co‐administration of TQ with BPA reduced the elevated serum levels of cholesterol, TG, LDL‐C, ALT, AST, and ALP. In line with our results, it was reported that oral administration of TQ (25, 50, 100 mg/kg, 2 weeks) reduced serum cholesterol, TG, LDL‐C, ALT, and AST levels in olanzapine‐treated rats, and the authors suggested that TQ protected liver tissue against hepatotoxic effects of olanzapine (Bilgic et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study displayed that co‐administration of TQ with BPA reduced the elevated serum levels of cholesterol, TG, LDL‐C, ALT, AST, and ALP. In line with our results, it was reported that oral administration of TQ (25, 50, 100 mg/kg, 2 weeks) reduced serum cholesterol, TG, LDL‐C, ALT, and AST levels in olanzapine‐treated rats, and the authors suggested that TQ protected liver tissue against hepatotoxic effects of olanzapine (Bilgic et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, liver from the olanzapine group showed large fat droplets in perinuclear region, between cisternae of the rough endoplasmic reticulum, and in the space of Disse 99. In a more recent study, olanzapine-administered (for 2 weeks) rats showed severe liver damage indicated by loss of normal architecture, vacuolar degeneration of hepatocytes and fatty changes in the liver 100. In a study from our group, daily intraperitoneal injection of clozapine for 6 weeks significantly increased plasma levels of triglycerides, led to hepatic steatosis and fibrosis along with increased activities of alanine aminotransferase and aspartate aminotransferase in male Wistar rats, but showed no effects on blood glucose, insulin levels, and total cholesterol 101…”
Section: Metabolic Effects and Nafld Of Aaps In Animal Studiesmentioning
confidence: 92%
“…The volatile lipidic fraction of Nigella sativa possesses insulinotropic properties, as shown through its maintenance of β-cell integrity in the pancrease [10]. It has been reported that black cumin seed oil (thymoquinone) produced significant decrease in serum glucose, triglycerides (TG), total cholesterol (TC), low density lipoproteincholesterol (LDL), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, when compared to the untreated diabetic rats [11].…”
Section: Introductionmentioning
confidence: 99%